2021
DOI: 10.1002/cey2.134
|View full text |Cite
|
Sign up to set email alerts
|

A review of carbon dots and their composite materials for electrochemical energy technologies

Abstract: Carbon dots (CDs) and their composites as energy storage materials and electrocatalysts have emerged as new types of quasi‐zero‐dimensional carbon materials. CDs can provide a large specific surface area, numerous electron–electron hole pairs, adjustable heteroatom doping, rich surface functional groups, and so on. However, the roles and functional mechanisms of CDs and their composite materials in the enhancement of electrochemical performance remain unclear and need to be understood in depth. Based on the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 172 publications
1
64
0
Order By: Relevance
“…Similarly, we found that the CDs in rice electrolyte increased the specific capacitance by 163 % [16] . These positive effects offered by the CDs came from the unique surface properties and nanometer size of the CDs, leading to favorable ion adsorption and wettability of the electrode/electrolyte interface, thereby facilitating charge transport and storage [31] . Therefore, herein, the CDs were prepared from bagasse and leaves and the effects of CDs as additives in molasses electrolyte, which have never been investigated previously, were explored in this present work (Figure 1).…”
Section: Introductionsupporting
confidence: 52%
“…Similarly, we found that the CDs in rice electrolyte increased the specific capacitance by 163 % [16] . These positive effects offered by the CDs came from the unique surface properties and nanometer size of the CDs, leading to favorable ion adsorption and wettability of the electrode/electrolyte interface, thereby facilitating charge transport and storage [31] . Therefore, herein, the CDs were prepared from bagasse and leaves and the effects of CDs as additives in molasses electrolyte, which have never been investigated previously, were explored in this present work (Figure 1).…”
Section: Introductionsupporting
confidence: 52%
“…3A shows the structure of traditional capacitors and supercapacitors, SCs are composed of electrodes immersed in the electrolyte, and a diaphragm electrically isolates the electrodes. According to different energy storage mechanisms, SCs can be divided into two types: double-layer capacitors (DLCs) represented by adsorption-desorption energy storage, and the other is pseudocapacitors materials represented by hydrogen storage by a redox reaction [48,101]. Compared with traditional batteries, the lower energy density of SCs limits the development of their practical applications.…”
Section: Progress Of Quantum Dots In Supercapacitorsmentioning
confidence: 99%
“…Carbon /graphene quantum dots (CQDs or GQDs) retain the characteristics of carbon materials' stable chemical properties and have quantum tunneling effect, size effect, and surface effect. It has a strong adsorption capacity for electrolyte ions, and it has a wide range of development prospects in SCs [95,98,101,102]. Table 1 summarizes carbon-based quantum dots in enhancing supercapacitors in recent years.…”
Section: Progress Of Quantum Dots In Supercapacitorsmentioning
confidence: 99%
“…The term “carbon dots” (CDs) usually refers to carbon or graphene quantum dots (CQDs or GQDs, respectively), carbon nanodots, or polymer dots [ 1 ]. As a new type of carbon nanomaterial, CDs are defined as dispersed spheroidal carbon particles less than 10 nm in diameter with fluorescence properties [ 2 ].…”
Section: Introductionmentioning
confidence: 99%